Inflation targeting and price-level-path targeting in the GEM: Some open economy considerations - Donald Coletti; René Lalonde; Dirk Muir (Bank of Canada, 2008)
This paper compares the performance of simple inflation targeting (IT) and price-level path targeting (PLPT) rules to stabilize the macroeconomy, in response to a series of shocks, similar to those seen in Canada and the United States over the 1983 to 2004 period. The analysis is conducted in a two-country (Canada and the United States), two-sector (tradables and nontradables) version of the International Monetary Fund's Global Economy Model (GEM). The authors conclude that PLPT is slightly preferred to IT for delivering macroeconomic stability, as it delivers a reduction in inflation and nominal interest rate volatility, at the expense of slightly higher output gap variability. When the analysis is restricted to the shocks that have been most important for explaining movements in Canada's terms of trade over this period, PLPT is still preferred to IT. The authors also show that their results are sensitive to the interaction between the relative importance of the different types of macroeconomic shocks that hit the economy, and the extent to which price and wage setting is forward looking. Lastly, the authors demonstrate that the choice of monetary policy framework in the United States does not affect the relative merits of PLPT versus IT in Canada.
Keywords: C51; C52; E17; E31; E52; 330; Economic models; Inflation: costs and benefits; Inflation and prices; Monetary policy framework; Inflation Targeting; Preisniveaustabilität; Gesamtwirtschaftliche Produktion; Zwei-Länder-Modell; Mehr-Sektoren-Modell; Ökonometrisches Makromodell; Dynamisches Gleichgewicht; Kanada; USA